A room temperature rechargeable Li–LiNO 3 battery with high capacity - Zhengqiang Hu; Fengling Zhang; Feng Wu; Li Li; Renjie Chen (Proceedings of the National Academy of Sciences, 2025)
Lithium-ion batteries (LIBs) have become advanced energy storage technologies; however, specific capacity remains limited by the active materials in cathodes. Here, we report Li–LiNO 3 batteries (LNBs) where LiNO 3 in electrolyte serves as both active materials and ion conductor at room temperature. LNBs operate on a highly reversible redox between NO 3 − and NO 2 − , which results in an impressive areal capacity of 19 mAh cm −2 at a plateau voltage of 1.75 V. Furthermore, the pouch cell exhibits stable cycling at a capacity of 100 mAh. This research underscores the potential of LNBs for high-capacity energy storage.